Bioinspired Design of Building Materials for Blast and Ballistic Protection - Yu-Yan Sun; Zhi-Wu Yu; Zi-Guo Wang (Advances in Civil Engineering)
Nacre in abalone shell exhibits high toughness despite the brittle nature of its major constituent (i.e., aragonite). Its specific structure is a major contributor to the energy absorption capacity of nacre. This paper reviews the mechanisms behind the performance of nacre under shear, uniaxial tension, compression, and bending conditions. The remarkable combination of stiffness and toughness on nacre can motivate the development of bioinspired building materials for impact resistance applications, and the possible toughness designs of cement-based and clay-based composite materials with a layered and staggered structure were discussed.